Efforts to Improve Reading Skills By Using the Aloud Reading Method in Class XI Students in Madrasah Aliyah Negeri 2 Gorontalo Regency - Rahmawati, Rahmawati; Bt. Hj. Bahri, Ratni; Paputungan, Zulkifli (Yayasan Daarul Qimmah Gorontalo, 2022)
The purpose of the study was to find out that learning using the reading aloud method can improve reading skills in Arabic learning in class XI students of Madrasah Aliyah Negeri 2 Gorontalo Regency. This research was carried out in two cycles with data analysis techniques of descriptive and quantitative qualitative approaches. The data collection techniques used are observation, interview, test, and documentation. Subject research is a class XI science student with a total of 22 students. The research design used is the Kemmis and McTaggart model which is carried out through four stages, namely planning, implementing, observation, and reflection. From the results of data analysis, the conclusions obtained from this study are: the average pre-test result is 42.23 and the average result of the post-test cycle I is 63.13. Furthermore, the average post-test result of cycle II was 84.86. With the number of students who completed the pre-test was 0 and the students who failed 22, then in the first cycle, the number of students who completed the post-test was 5 and students who failed 17, and cycle II students who completed 19 and students who failed 3. With the successful results of pre-test 0%, post-test cycle I 23%, and post-test cycle II 86%. Thus, it can be concluded that the use of the reading aloud method can improve reading skills in Arabic learning in class XI students of Madrasah Aliyah Negeri 2 Gorontalo Regency.